2020
DOI: 10.15586/jkcvhl.2020.131
|View full text |Cite
|
Sign up to set email alerts
|

Renal Manifestations of Tuberous Sclerosis Complex

Abstract: Tuberous sclerosis complex (TSC) is a genetic condition caused by a mutation in either the TSC1 or TSC2 gene. Disruption of either of these genes leads to impaired production of hamartin or tuberin proteins, leading to the manifestation of skin lesions, tumors, and seizures. TSC can manifest in multiple organ systems with the cutaneous and renal systems being the most commonly affected. These manifestations can secondarily lead to the development of hypertension, chronic kidney disease, and neurocognitive decl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 88 publications
0
7
0
1
Order By: Relevance
“…TSC renal lesion pleiotropy is enigmatic. AMLs are of clonal origin (Green et al, 1996;Karbowniczek et al, 2003) and biallelic inactivation of TSC1 or TSC2 is sufficient for pathogenesis (Giannikou et al, 2016;Martin et al, 2017;Qin et al, 2011), yet pathological analyses of the TSC kidney have shown remarkable diversity in lesion morphology, size, cellular composition, and molecular expression (Ashfaq et al, 1993;Chan et al, 1993;Chilosi et al, 2009;D'Armiento et al, 2016;Jungbluth et al, 1999;Nair et al, 2020;Siroky et al, 2011). While between-patient disease expressivity is likely attributable to variable mosaicism (Giannikou et al, 2019;Green et al, 1994;Tyburczy et al, 2015;Verhoef et al, 1999) and greater clinical severity conferred by TSC2 mutations over TSC1 (Curatolo et al, 2015;Dabora et al, 2001), the cellular mechanisms underlying within-patient lesion diversity is elusive.…”
Section: Introductionmentioning
confidence: 99%
“…TSC renal lesion pleiotropy is enigmatic. AMLs are of clonal origin (Green et al, 1996;Karbowniczek et al, 2003) and biallelic inactivation of TSC1 or TSC2 is sufficient for pathogenesis (Giannikou et al, 2016;Martin et al, 2017;Qin et al, 2011), yet pathological analyses of the TSC kidney have shown remarkable diversity in lesion morphology, size, cellular composition, and molecular expression (Ashfaq et al, 1993;Chan et al, 1993;Chilosi et al, 2009;D'Armiento et al, 2016;Jungbluth et al, 1999;Nair et al, 2020;Siroky et al, 2011). While between-patient disease expressivity is likely attributable to variable mosaicism (Giannikou et al, 2019;Green et al, 1994;Tyburczy et al, 2015;Verhoef et al, 1999) and greater clinical severity conferred by TSC2 mutations over TSC1 (Curatolo et al, 2015;Dabora et al, 2001), the cellular mechanisms underlying within-patient lesion diversity is elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Angiomyolipomas, with or without associated tuberous sclerosis, tend to occur in females. Microscopically, they are composed of a variable mixture of mature adipose tissue, blood vessels, and smooth muscle [20]. In the present patient, the classic morphology of the smaller tumor on H&E and co-expression of 2 different IHC markers that confirm the myelomelanocytic lineage (SMA and melan-A) was sufficient to establish the diagnosis of angiomyolipoma for the smaller tumor.…”
Section: Discussionmentioning
confidence: 51%
“…Although renal cysts are generally asymptomatic, they can more frequently cause subsequent hypertension with rapid progression to end-stage renal failure. 10 , 12 Thus, screening and treating hypertension and proteinuria, as well as preserving renal tissue, with the use of mTOR inhibitors, and sparing of renal tissue are advocated. 11 , 13 …”
Section: Discussionmentioning
confidence: 99%